An adolescent with herpes simplex encephalitis, presenting with mild symptoms and rapid deterioration: A case report. (December 2020) - Stepien, Natalia; Weseslindtner, Lukas; Seidl, Rainer; Geldner, Julia; Golej, Johann; Schmook, Maria-Theresa; Peyrl, Andreas
Headaches in children are a common, but unspecific symptom that can have many underlying causes, ranging from unspecific tension headache through migraine and up to encephalitis and intracranial hypertension. We present the case of a 14-year-old boy who presented to our emergency department with headache, nausea as well as vomiting and developed seizures later on. The initial diagnosis was complicated by a magnetic resonance imaging which did not show any signs of inflammation, but was of limited informative value due to orthodontic appliances. Despite the unremarkable imaging, prophylactic antiviral and antibiotic treatment was started after lumbar puncture. Herpes simplex virus as well as human herpes virus 7 were confirmed in the cerebrospinal fluid. Although both viruses are ubiquitous, severe infections are a rare complication. Immunodeficiency syndromes are predisposing factors for serious complications and genetic analysis of UNC93B and TLR-3 might be helpful for decision-making. No genetic or immunologic predisposition was found in our patient. The patient's condition deteriorated rapidly, so he had to be admitted to the pediatric intensive care unit, where he was intubated and his antiviral treatment with acyclovir was extended by foscarnet. After prolonged mechanical ventilation, he slowly improved. With intensive neurorehabilitation, he could finally return to his daily life activities 3 months after diagnosis. Despite headaches being an unspecific symptom, the possibility of a herpes simplex virus encephalitis should always kept in mind, especially in patients presenting with additional symptoms such as vomiting, altered mental status and/or focal neurological deficits. An initial magnetic resonance imaging might be misleading if orthodontic appliances are in place. Initiation of treatment without delay is crucial for neurologic outcome of herpes simplex virus encephalitis.